Ultrasonic Treatment Increases Extraction Rate of Common Bean (Phaseolus vulgaris L.) Antioxidants - Qiong-Qiong Yang; Ren-You Gan; Ying-Ying Ge; Dan Zhang; Harold Corke (MDPI AG, 2019)
The feasibility of improving the extraction rate of common bean antioxidants by ultrasonic treatment was investigated. Scanning electron microscopy (SEM) and spectrum Fourier transform infrared spectrophotometer (FT-IR) analysis revealed that ultrasonic treatment substantially altered the cellular structure of common bean seed, resulting in increased surface area, eroded cell walls, and greater exposure of cellulose and hemicellulose. The highest antioxidant activity was obtained at optimal extraction conditions (68 min, 55% acetone, 36:1 liquid to solid ratio, 30 ℃, and 480 W) which were optimized by response surface methodology. In terms of the extraction rate of common bean antioxidants, ultrasound-assisted extraction (UAE) exhibits about seven-fold higher extraction efficiency than conventional solvent extraction (CSE). In addition, 10 phenolic compounds in the common bean extracts were detected and quantified by high performance liquid chromatography (HPLC), including protocatechuic acid, catechin, chlorogenic acid, epicatechin, ferulic acid, coumarin, rutin, myricetin, cinnamic acid, and genistein. In summary, ultrasonic treatment is an ideal candidate methodology for improving the extraction rate of common bean antioxidants.